ANALISIS PEMBAGIAN TUGAS KARYAWAN DALAM MENINGKATKAN EFEKTIVITAS KERJA MELALUI KOMUNIKASI ORGANISASI PADA PELAKSANAAN REMOTE WORKING DI PT. TANAIR MEDIA SERUNI - BUDI SUSWANTO (Institut Bisnis Muhammadiyah Bekasi, 2020)
Organizational communication began to experience changes in technology-based companies, because it was built by developments in technology and information technology. Where organizational communication was previously built based on physical meetings, is now done online in a remote work system. The research was conducted to analyze the division of duties of employees in improving work through organizational communication in the implementation of remote work at PT Tanair Media Seruni. Observation data through direct observation in the field, in-depth interviews, and documentation. The research was conducted using a qualitative approach with the constructivism paradigm. Using authority theory and organizational communication theory in research. From the results of successful research, presenting the task carried out by technology-based work communication, has now become a necessity. Gadgets seem to be an inseparable device from our work that uses a remote work system. The technology used also does not hinder the management of work communication coordination in presenting tasks. For remaining invincible with crop, organization, action and control. In this way, the entire effective work process can go well.